BLOCK DOUBLE DOMINATION IN GRAPHS - MUDDEBIHAL, M. H.; GADE*, SUHAS P. (International Journal of Mathematical Archive, 2018)
For any graph , the block graph of a graph is the graph whose set of vertices is the union of the set of blocks of in which two vertices are adjacent if and only if the corresponding blocks of are adjacent. A subset of is double dominating set of if for every vertex that is is in and has at least one neighbour in or is in and has at least two neighbours in The block double dominating number is a minimum cardinality of block double dominating set. In this paper, we establish upper and lower bounds on in terms of elements of and other dominating parameters of are obtained.